Мерчандайзинг – эффективная маркетинговая технология продвижения страховых продуктов - Смирнова, Е. А. (Культура народов Причерноморья, 2014)
В статье рассмотрены теоретические основы понятия «мерчандайзинг», определены цель и задачи мерчандайзинга в страховании. Рассмотрены составляющие элементы мерчандайзинга, применяемые при составлении планов продвижения различных страховых продуктов в страховой компании. Проанализированы варианты организационно-штатной структуры мерчандайзинга в страховых организациях, а также выделены преимущества и недостатки рассмотренных вариантов. У статті розглянуто теоретичні основи поняття «мерчандайзинг», визначено мета і завдання мерчандайзингу в страхуванні. Розглянуто складові елементи мерчандайзингу, застосовувані при складанні планів просування різних страхових продуктів в страхової компанії. Проаналізовано варіанти організаційно-штатної структури мерчандайзингу в страхових організаціях, а також виділено переваги та недоліки розглянутих варіантів. In modern conditions with increased competition in the insurance market and the number of insurance companies, increasing competition between insurance companies in the insurance industry leads to the fact that in front of them face the problem of finding such methods for forming an insurance company a competitive advantage compared to the other, which would strengthen its own position in the competitive struggle for the client-insured. One way to create such benefits is an insurance merchandising the result of which is to stimulate the desire of consumers to choose and buy the promoted insurance product (service). The article analyzes the theoretical foundations of the concept of «merchandising». Formed the goal of insurance merchandising. Integrated approaches to the study of merchandising have helped to define the tasks merchandising in insurance. Considered elements of merchandising, applied in the preparation of plans for the promotion of various insurance products in the insurance company. Analyzed options for the organizational structure of merchandising in insurance companies, as well as the advantages and disadvantages of the considered options. It is determined that a professionally decorated interior, modern design office of the insurance company, take into account using all of the factors of psychological, emotional impact on the behavior of the prospective insured, enhance the profitability of the insurance business. It is noted that application of the insurance merchandising is one of the most important tasks of the insurance company.